Feasibility Analysis of Roof PLTS Development For Electricity Fulfillment at Station - Rachman, Natriya Faisal; Firdhous, Cahya (Nusantara Publisher, 2024)
Lemah Abang Station is a station located in Cikarang, this station is used for Cikarang-Cikampek, Cikarang-Purwakarta trips and KRL trips. To support the general national energy plan (RUEN) through Presidential Regulation No.79 of 2014, the Government of Indonesia has set a policy of increasing the share of renewable energy in the national energy mix to 23% by 2025. To support this effort, PLN's electrical power is converted to solar panels. This can be seen from the abundant solar energy potential in Cikarang, namely 5,040 Kwh/m2/day with a total duration of 2-9 hours of solar radiation per day. The solar panels that will be made have a capacity of 20 kWp using 48 units of 450Wp solar panels. Other components needed are a 20 kW inverter, 8 12V 200Ah batteries, kWh Exim, Solar Charger. Based on the economic analysis, the cheapest energy cost is 1762/kWh. In addition, the investment analysis for the construction of solar panels with the NPV, IRR, PI, and DPP methods is declared feasible to be carried out.